Ultra-thin liquid film with shear and the influences on thermal energy transfer at solid–liquid interfaces of simple liquid methane in contact with (110) surface structure of face-centred cubic lattice (FCC) - Saleman, Abdul Rafeq; Zakaria, Mohamad Shukri; Jumaidin, Ridhwan; Maslan, Mohd Nazmin (Penerbit Akademia Baru, 2021)
Thermal energy transfer (TET) is the main performance of contact interfaces which has been studied at a molecular level. Several investigations on TET were accomplished, however, the influences of sheared liquid and liquid film thickness on TET have not been sufficiently examined. Thus, this paper analyses the influences of liquid film thickness on TET across solid–liquid (S-L) interfaces. Two liquid film thicknesses (Lz) of 30 Å and 60 Å have been evaluated, and two shear directions (x-and y-directions) have been tested in the simulation system. It has been found that there is no significant difference in the density distribution of liquid regardless of the shear directions for the same Lz. However, there are differences in the density distribution of liquid between Lz of 30 Å and 60 Å. Based on the results its suggests that, the cut-off of the temperature and velocity at the contact interfaces of solid and liquid is substantially influences by the shear applied to the liquid and the liquid film thickness of the simulation system. It is found that, there are a significant different in the thermal boundary resistance (TBR) for Lz of 30 Å and 60 Å for cases liquid sheared in the x-direction. Whereas TBR for Lz of 30 Å and 60 Å sheared in the y-direction have no significant difference. In conclusion, the TET is affected by the velocity cut-off at the contact interfaces of solid and liquid where larger velocity discontinuity exhibits higher TBR.